Outcomes of asymptomatic and symptomatic rheumatic heart disease - Zühlke, Liesl Joanna (University of Cape Town, 2016)
Includes bibliographical references === Rheumatic Heart Disease (RHD) is a leading cause of heart disease in children and young adults in the developing world, with significant associated morbidity and mortality. Early secondary prophylaxis may retard the deleterious progression from its antecedent, acute rheumatic fever to permanent heart valve damage, and thus several echocardiographic screening programmes to detect asymptomatic RHD and institute early prophylaxis have been conducted. While effective interventions are available for ameliorating the effects of RHD, research on their use in different settings is scant. Key questions remain regarding the natural history of asymptomatic RHD and the optimal method for early detection. In addition, there is a lack of contemporary estimates of mortality and morbidity among the symptomatic population in the developing world. The primary purpose of the thesis was to determine the outcomes of asymptomatic and symptomatic RHD. More specifically, I sought to quantify the incidence, prevalence and outcomes of RHD in South Africa over the past two decades, determine the natural history of asymptomatic RHD and validate a focused protocol for screening in schoolchildren from Cape Town. In addition, I determined the baseline characteristics, prevalent sequelae and gaps in evidence-based implementation in children and adults from14 developing countries. Finally, I investigated the independent predictors for mortality and morbidity of RHD over a two-year period in patients from Cape Town, South Africa. My thesis has five key findings. Firstly, a systematic review of the literature showed that the incidence and prevalence of RHD over the past two decades in South Africa remains high, although there is evidence of falling cause-specific mortality at a population level. Secondly, asymptomatic RHD has a variable natural history that ranges from regression to a normal state, to persistence of disease, and progression to symptomatic RHD. Thirdly, a focused hand-held echocardiography protocol shows promising levels of sensitivity and specificity for detecting subclinical RHD. Fourthly, the baseline data from the global rheumatic heart disease registry demonstrates significant gaps in the implementation of medical and surgical interventions of proven effectiveness in low- and middle-income countries. Finally, the annual mortality rate for children and adults with RHD in Cape Town over a two-year period is 4.1%with cardiovascular events occurring at a rate of 0.18 events per patient per year. The findings encapsulated in this thesis have important implications for policy, practice and research related to the management of asymptomatic and symptomatic RHD in the world.